Proceso de diagnóstico de la discapacidad intelectual. - Pozo Mite, Ana Paula (My University, 2019)
Intellectual disability is a disorder that affects the intellectual functioning and adaptive capacities of the individual, which occurs during the stage of human development. Performing a diagnostic process to identify this disorder involves using current concepts regarding diagnostic criteria and arrive at the main purpose of the same: to perform an intervention with expectations according to the strengths and weaknesses of the patient. The objective of this work is to describe evaluation tools, selected through the current bibliographic review, that provide guidelines to the professional to perform a diagnostic process capable of directing an intervention according to the needs and capabilities of children up to 7 years, who come for psychological consultation. The reagents mentioned in this essay are subdivided into two categories according to the age of the patient: developmental scales and intelligence scales. Both categories fulfill the function of auxiliary in the diagnosis of an intellectual disability and in the support so that the multidisciplinary team that intervenes in the study of the case is allowed to open the referential discussion after an exhaustive exploration from different perspectives. The importance of making an accurate diagnosis lies in the intervention that will be planned for the patient since it must be based on his strong faculties and his less developed characteristics.
La discapacidad intelectual es un trastorno que afecta el funcionamiento intelectual y las capacidades adaptativas del individuo, que se presenta durante la etapa del desarrollo del ser humano. Realizar un proceso de diagnóstico para identificar este trastorno, implica utilizar conceptos actuales referentes a los criterios diagnósticos y llegar al propósito principal del mismo: realizar una intervención con expectativas acorde a las fortalezas y debilidades del paciente. El presente trabajo tiene como objetivo describir herramientas de evaluación, seleccionadas mediante la revisión bibliográfica actual, que brinden pautas al profesional para que realice un proceso de diagnóstico capaz de direccionar una intervención acorde a las necesidades y capacidades de niños de hasta 7 años, que acuden a consulta psicológica. Los reactivos que se mencionan en este ensayo, se subdividen en dos categorías según la edad del paciente: las escalas de desarrollo y las escalas de inteligencia. Ambas categorías cumplen la función de auxiliar en el diagnóstico de una discapacidad intelectual y en el apoyo para que el equipo multidisciplinario que interviene en el estudio del caso se permita abrir la discusión referencial luego de una exhaustiva exploración desde diferentes perspectivas. La importancia de realizar un diagnóstico preciso, radica en la intervención que se planificará para el paciente ya que debe estar fundamentado en sus facultades fuertes y sus características menos desarrolladas.
Keywords: DISCAPACIDAD INTELECTUAL; PROCESO; DIAGNOSTICO; INTERVENCION